2010
DOI: 10.1109/tnb.2010.2053770
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Iron Oxide–Silica Composite Particles Using Mesoporous SBA-15 Silica as Template and Their Internalization Into Mesenchymal Stem Cell and Human Bone Cell Lines

Abstract: A new procedure for preparing iron oxide-silica nanocomposite particles using SBA-15 mesoporous silica as a template is described. These composite materials retained the 2-D hexagonal structure of the SBA-15 template. Transmission electron micrograms of the particles depicted the formation of iron oxide nanocrystals inside the mesochannels of SBA-15 silica framework. Powder x-ray diffraction showed that the iron oxide core of the composite particles consists of a mixture of maghemite (gamma-Fe(2)O(3)) and heam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The positive role of silica (SiO 2 ) in bone integration and cell proliferation and the role of Fe 2 O 3 in cytotoxicity has been reported in the literature. 36,37 Nevertheless, further detailed studies are required to understand the cytotoxicity mechanisms of ZrSiO 4 −α-Fe 2 O 3 composites. Morphological Features.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The positive role of silica (SiO 2 ) in bone integration and cell proliferation and the role of Fe 2 O 3 in cytotoxicity has been reported in the literature. 36,37 Nevertheless, further detailed studies are required to understand the cytotoxicity mechanisms of ZrSiO 4 −α-Fe 2 O 3 composites. Morphological Features.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As shown in Figure (c), by increasing the calcination temperature, obvious peaks pertinent to α‐Fe 2 O 3 became appear. Therefore, it could be said that iron oxide amorphous phase or nanocrystalline iron oxide particles with diameter lower than five nanometer were present in final product . Also, using Scherrer equation, the crystallite size of 10 wt% nanocomposites calcined at 500 and 700°C were determined to be about 10 and 18 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Kostura and colleagues found that Feridex poly- L -lysine in fact inhibited chondrogenesis, yet this was not found with Feridex protamine [54,55]. Therefore, the effect of the transfection agent must be investigated further as it may interfere with the activities of the cell [56]. To overcome the limitations incurred by internalisation and the use of transfection agents, a technique known as magnetoelectroporation has been introduced [30].…”
Section: Labelling Of Stem Cells With Spionsmentioning
confidence: 99%